Replication of a Tetra-Stranded Genome : Mechanistic Scenarios and Minimal Enzymatic Constraints for Q-DNA - Barack Ndenga (Publisher, 2025)
Replication is the defining operation of any hereditary system. While duplex DNA replication relies on strand separation and template-directed synthesis, a canonical tetra-stranded genome cannot be replicated by a simple extension of this paradigm. In this work, I develop plausible replication cycles for Q-DNA, a canonical tetra-stranded hereditary polymer, and analyze the minimal mechanistic and enzymatic constraints required for faithful copying. I propose three classes of replication strategies— 2+2 strand separation, guide-strand replication, and partial-template replication—and derive testable predictions regarding intermediates, ion dependence, and replication asymmetries. This framework renders Q-DNA replication experimentally falsifiable and establishes replication as a decisive feasibility axis for tetra-stranded heredity.
Replication is the defining operation of any hereditary system. While duplex DNA replication relies on strand separation and template-directed synthesis, a canonical tetra-stranded genome cannot be replicated by a straightforward extension of this paradigm. The feasibility of tetra-stranded heredity therefore hinges on the existence of plausible replication cycles that are both mechanistically and energetically realistic. In this work, I develop a theoretical framework for the replication of Q-DNA, defined as a canonical tetra-stranded hereditary polymer, and propose several mechanistic replication scenarios. These include replication via 2+2 strand separation, guide-strand replication, and partial-template replication, each analyzed in terms of completeness, fidelity, energetic cost, and structural reset. I explicitly identify the minimal functional constraints required of a hypothetical Q-polymerase, emphasizing multi-strand recognition, geometry-aware synthesis, and strong dependence on ionic and environmental conditions rather than strict homology to modern DNA polymerases. The framework yields falsifiable predictions, including the existence of characteristic replication intermediates, asymmetric strand usage, and sharp dependence of replication efficiency on multivalent cation concentration and temperature cycling. By formulating replication as a closed, repeatable cycle subject to explicit physical constraints, this work establishes replication as the decisive criterion for evaluating Q-DNA as a viable hereditary system and positions tetra-stranded heredity within the broader context of theoretical biology, synthetic genetics, and origin-of-life research.